2016
DOI: 10.1016/j.polymer.2016.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Poly( N -2-(methacryloyloxy)ethyl pyrrolidone)-poly(benzyl methacrylate) diblock copolymer nano-objects via RAFT alcoholic dispersion polymerisation in ethanol

Abstract: were produced by polymerisation-induced self-assembly (PISA). Finally, a PNMEP 47 -PBzMA 243 diblock copolymer was synthesised via a convenient -whereby a PNMEP 47 macro-CTA was first prepared at 97% conversion, followed by in situ RAFT dispersion polymerisation of BzMA to produce diblock copolymer nano-objects. TEM analysis of aliquots taken during the diblock copolymer synthesis indicated a gradual evolution in copolymer morphology from spherical micelles after 1 h to a pure vesicle phase after 8 h via inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
(99 reference statements)
0
16
0
1
Order By: Relevance
“…Results showed that the k app value was reduced to 2/3 of that of the reaction with CTA-Me in DMF and that the reaction had an induction period t i ¼ 4.3 h. This result might derive from the slow chain transfer reaction of more stable 3 cyanopropyl radicals generated from CTA-Pr in the active/dormant equilibrium. 35,36 Nevertheless, this reaction affords controlled radical polymerization with narrow molecular weight distribution. In the case of polymerization of acrylamide monomers with shortbranched side chain (ptPA), the k app value was higher than that for pDDA (k app ¼ 6.4 Â 10 À5 s À1 in toluene, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the k app value was reduced to 2/3 of that of the reaction with CTA-Me in DMF and that the reaction had an induction period t i ¼ 4.3 h. This result might derive from the slow chain transfer reaction of more stable 3 cyanopropyl radicals generated from CTA-Pr in the active/dormant equilibrium. 35,36 Nevertheless, this reaction affords controlled radical polymerization with narrow molecular weight distribution. In the case of polymerization of acrylamide monomers with shortbranched side chain (ptPA), the k app value was higher than that for pDDA (k app ¼ 6.4 Â 10 À5 s À1 in toluene, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57] Thus it seems likely that the few cases where the onset of micellization has apparently coincided with the presence of higher order morphologies (rather than the formation of spheres) are actually artifacts caused by the ingress of hot solvent at elevated temperature into the nanoparticle cores. 21,[58][59][60] Each aliquot removed for these kinetic studies was also analyzed via GPC to assess the evolution of Mn and Mw/Mn during the DMA polymerization (see Figure 3b). A linear evolution of Mn with conversion was observed, as expected for a RAFT polymerization.…”
Section: Inspection Ofmentioning
confidence: 99%
“…For example, Cunningham and co-workers reported the RAFT dispersion polymerisation of benzyl methacrylate in ethanol using PNMEP as a steric stabiliser block. 16 Alternatively, PNMEP can be utilised as a core-forming block for RAFT dispersion polymerisation formulations conducted in n-dodecane. 17 Turbidimetry studies confirm that PNMEP exhibits inverse temperature solubility in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%